CD4 T cell differentiation in type 1 diabetes. (28th July 2015) - Walker, L. S. K.; von Herrath, M.
Summary: Susceptibility to type 1 diabetes is associated strongly with human leucocyte antigen (HLA) genes, implicating T cells in disease pathogenesis. In humans, CD8 T cells predominantly infiltrate the islets, yet their activation and propagation probably requires CD4 T cell help. CD4 T cells can select from several differentiation fates following activation, and this choice has profound consequences for their subsequent cytokine production and migratory potential. In turn, these features dictate which other immune cell types T cells interact with and influence, thereby determining downstream effector functions. Obtaining an accurate picture of the type of CD4 T cell differentiation associated with a particular immune‐mediated disease therefore constitutes an important clue when planning intervention strategies. Early models of T cell differentiation focused on the dichotomy between T helper type 1 (Th1) and Th2 responses, with type 1 diabetes (T1D) being viewed mainly as a Th1‐mediated pathology. However, several additional fate choices have emerged in recent years, including Th17 cells and follicular helper T cells. Here we revisit the issue of T cell differentiation in autoimmune diabetes, highlighting new evidence from both mouse models and patient samples. We assess the strengths and the weaknesses of the Th1 paradigm, review the data on interleukin (IL)‐17 production in type 1 diabetes and discuss emerging evidence for the roles of IL‐21 and follicular helper T cells in this disease setting. A better understanding of the phenotype of CD4 T cells in T1D will undoubtedly inform biomarker development, improve patient stratification and potentially reveal new targets for therapeutic intervention.